FEASIBILITY ANALYSIS OF DRAGON FRUIT (Hylocereus polyrhizus) FARMING IN THE ORGANIC VILLAGE OF BEJI VILLAGE, WONOGIRI REGENCY - Dewi, Tria Rosana; Wardani, Irma; Solikah, Umi Nur (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Dragon fruit plants are one of the horticultural products that are included in international commodities. Since entering the mid-2000s, dragon fruit has multiplied in various regions in Indonesia. Dragon fruit is one of the commodities whose prospects are increasing in the market. The increasing demand and consumption of dragon fruit cause the need for ways to increase productivity in several production centers. This study aimed to determine the feasibility of dragon fruit farming. The research was conducted in the Organic Village of Beji Village, Wonogiri Regency, with a descriptive method. The data analysis used were farming costs, revenue, income, and feasibility. Organic dragon fruit farming costs with a land area 1000m2 in the first year amounted to Rp.17,470,000, in the second year, amounted to Rp. 4,660,000, and in the third year, amounted to Rp. 3,370,000. Organic dragon fruit farming revenue with a land area 1000m2 in the first year amounted to Rp. 2,304,000, in the second year, amounted to Rp. 11,520,000, and in the third year, amounted to Rp. 10,800,000. The income level of organic dragon fruit farming with a land area of 1000m2 in the first year amounted to Rp. 15,166,000, in the second year amounted to Rp. 6,860,000, and in the third year, it amounted to 7,430,000. The feasibility of organic dragon fruit farming with a land area of 1000m2 in the first year amounted to -0.87, in the second year amounted to 1.48, and in the third year amounted to 2.20. Keywords: Farming, Feasibility, Dragon Fruit, Organic